Konsep Anak Tentang Tuhan - Subandi, M.A. (Perpustakaan Kalam, 2006)
Religious Psychologists, commonly believe that human being has religious instinct; a ptentiality that naturrally brings human to a religious life. The islamic psychologists also agree that human are born with fitrah which mean, bassic believe in the existence of God